The Influence of Patient Experience on Outpatient Revisit Intention at Hospital X - Arfadina Dwi Rosalina; Hermanto Wijaya; Rina Budi Kristiani; Yura Witsqa Firmansyah (Jurnal Kesehatan dan Kedokteran, 2026)
Patient experience is an important indicator of healthcare quality because it reflects patients’ perceptions of communication, responsiveness, comfort, and overall service delivery during the care process. A positive patient experience may encourage patients to return to the same healthcare facility, making it an essential factor for hospitals seeking to improve patient retention and service quality. Objective: This study aimed to analyze the effect of patient experience on outpatient revisit intention at Hospital X by examining four dimensions: nurse communication, physician communication, service responsiveness, and physical comfort. Methodology: This study used an analytical observational design with a cross-sectional approach. A total of 57 outpatients were selected using accidental sampling. Data were collected using a structured questionnaire and analyzed using Binary Logistic Regression. Findings: The results showed that physician communication received the highest proportion of good ratings (75.4%), followed by nurse communication (63.2%), while service responsiveness and physical comfort were mostly rated as adequate (59.6%). Most respondents (94.7%) expressed an intention to revisit the hospital. Among the four dimensions examined, service responsiveness was the only dimension significantly associated with revisit intention (p = 0.018; Exp(B) = 7.172). Implications: These findings imply that improving service responsiveness, reducing waiting time, and ensuring timely assistance may strengthen outpatient loyalty and encourage repeat visits. Originality: The originality of this study lies in its specific examination of selected patient experience dimensions rather than assessing patient experience as a single general construct, thereby providing more detailed evidence on which service aspect should be prioritized to improve outpatient revisit intention.